2011
DOI: 10.1007/s00125-011-2111-y
|View full text |Cite
|
Sign up to set email alerts
|

Unconditioned and conditioned effects of intranasally administered insulin vs placebo in healthy men: a randomised controlled trial

Abstract: Aims/hypothesis In humans, the intranasal route allows insulin to reach the brain while maintaining peripheral euglycaemia. Our aims were to examine acute (unconditioned) effects of central insulin on normal-range blood glucose and hormones in men, and to find out whether the effects of intranasal insulin can be learnt via classical conditioning. Methods In a randomised controlled trial, 32 healthy normalweight men (mean age 24.2 [SEM 0.5], mean BMI 22.4 [0.3]) received a conditioned stimulus (CS) and six admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 13 publications
1
55
1
Order By: Relevance
“…For humans, the issue is not yet clear. Recently, nasal insulin application was demonstrated to influence noradrenaline (norepinephrine) levels, an indicator of sympathetic nervous system activity [47]. However, a smaller study found no effect of intranasal insulin on muscular sympathetic nervous activity [48].…”
Section: Discussionmentioning
confidence: 99%
“…For humans, the issue is not yet clear. Recently, nasal insulin application was demonstrated to influence noradrenaline (norepinephrine) levels, an indicator of sympathetic nervous system activity [47]. However, a smaller study found no effect of intranasal insulin on muscular sympathetic nervous activity [48].…”
Section: Discussionmentioning
confidence: 99%
“…The experimental group is then re-exposed to the CS during evocation and alterations in neuroendocrine functions (e.g., concentrations of adrenaline, glucose, cortisol, insulin, norepinephrine, glucagon, vasopressin, ACTH, somatropin) 710 are analyzed, reflecting the conditioned response. Although learned placebo responses in neuroendocrine functions have been demonstrated in experimental animals (Ader, 1976;Buske-Kirschbaum et al, 1996;Janz et al, 1996;Pacheco-Lopez et al, 2004), there are few studies reporting these effects in humans, and those that do mainly employed insulin as a US measuring blood glucose or insulin levels as a conditioned response (Fehm-Wolfsdorf et al, 1993;Stockhorst et al, 1999Stockhorst et al, , 2004Stockhorst et al, , 2011Klosterhalfen et al, 2000;reviewed in Wendt et al, 2014b). Two human studies reported conditioned changes in plasma cortisol concentrations.…”
Section: E Neuroendocrine Responsesmentioning
confidence: 99%
“…Concerning the studies on conditioning of immune functions, 5 studies addressed conditioned immunosuppression (31% of all studies) [19][20][21][22][23] , 3 studies addressed conditioned immunostimulation (19%) [24][25][26] , and 3 studies addressed conditioned allergic responses (19%) [9,27,28] . Of the studies on conditioning of endocrine outcomes, 4 (25%) addressed conditioned glycemic responses [29][30][31][32] and the remaining study addressed conditioned cortisol (6%) [33] .…”
Section: Conditioning Paradigmsmentioning
confidence: 99%
“…The participants in 13 studies were healthy volunteers (81%) [19][20][21][22][23][24][25][26][29][30][31][32][33] , whereas 3 studies (19%) included participants who were allergic to either pollen [27] or house dust mites [9,28] .…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation